Novel labyrinthulomycete lineages in aquatic moss pillars inhabiting an Antarctic lake - Ryosuke, Nakai; Yuiki, Takahashi; Masaki, Yoshida; Megumu, Tsujimoto; Atsushi, C. Suzuki; Sakae, Kudoh; Satoshi, Imura (2017)
第8回極域科学シンポジウム/個別セッション：[OB] 極域生物圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object